Wheat silage partially replacing oaten hay exhibited greater feed efficiency and fibre digestion despite low feed intake by feedlot lambs - Zhao-Yang Cui; Wen-Juan Li; Wei-Kang Wang; Qi-Chao Wu; Yao-Wen Jiang; Ailiyasi Aisikaer; Fan Zhang; He-Wei Chen; Hong-Jian Yang (Animal Nutrition, 2023)
This study aimed to investigate the feeding effect of wheat silage on growth performance, nutrient digestibility, rumen fermentation, and microbiota composition in feedlot lambs. Sixty-four male crossbred Chinese Han lambs (BW = 27.8 ± 0.67 kg, 3 months of age) were randomly assigned to four ration groups with wheat silage replacing 0% (WS0), 36% (WS36), 64% (WS64), and 100% (WS100) of oaten hay on forage dry matter basis. The concentrate-to-forage ratio was 80:20 and the feeding trial lasted 52 d. Increasing wheat silage inclusion linearly decreased dry matter intake by 4% to 27% (P < 0.01). However, increasing the wheat silage replacement of oaten hay by no more than 64% improved the feed efficiency by 14% as noted by the feed-to-gain ratio (P = 0.04). Apparent digestibility of organic matter (P < 0.01), neutral detergent fibre (P = 0.04) and acid detergent fibre (P < 0.01) quadratically increased. Ammonia nitrogen (P = 0.01) decreased while microbial protein production (P < 0.01) increased with the increase of wheat silage inclusion. Total volatile fatty acids concentration increased quadratically with the increase of wheat silage inclusion (P < 0.01), and the highest occurred in WS64. The molar proportion of acetate (P < 0.01) and acetate-to-propionate ratio (P = 0.04) decreased while butyrate (P < 0.01) and isovalerate (P = 0.04) increased. Increasing wheat silage inclusion increased the Firmicutes-to-Bacteroidota ratio by 226% to 357%, resulting in Firmicutes instead of Bacteroidota being the most abundant phylum. The relative abundance of cellulolytic Ruminococcus numerically increased but that of amylolytic Prevotella (P < 0.01) decreased as increasing wheat silage inclusion. Taken together, increasing wheat silage replacement of oaten hay by no more than 64% exhibited greater feed efficiency and fibre digestion despite low feed intake by feedlot lambs due to the change of Firmicutes-to-Bacteroidota ratio in the rumen.